Ulayat Land as a Wakf Object According to Law No 41 Year 2004 Case Study Todairi District Berampu - Muhammad Aidil Hanafi; Md. Yadi Harahap; Ramadhan Shahmedi Siregar (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
Waqf is one of the Islamic philanthropy that carries the common interest. In the order of life, the Muslim community in the district of Berampu, Dairi district, is a Muslim minority. But even so, the spirit and practice of carrying out their religion is very strong. In this regard, including the concern is the spirit of the community to develop and increase the benefits of ulayat land, ulayat land is also waqf.This research aims to Knowing the position of ulayat land as an object of waqf by the people of Berampu sub-district, Dairi district in terms of Law No. 41 of 2004. To answer these problems, a field research was conducted with a qualitative research analysis model which was analyzed through a positive legal theory approach and Islamic law. Based on the results of the study it is known that the implementation of customary land waqf carried out by the people of the Berampu sub-district, as the researchers described earlier is not in accordance with Law No. 41 of 2004 concerning waqf. This is because 1)Customary land is not an object of waqf. This can be seen in PP No. 24 of 1997 in lieu of PP No. 10 of 1961 which states that customary land is not the object of land registration, while in PP no. 24 of 1997, waqf land is the object of land registration. So from this it can be seen that ulayat land is not actually an object of waqf. Because the object of waqf is land that has been registered in accordance with applicable regulations. 2) The practice of waqf carried out by the community of Berampu sub-district, Dairi Regency, is still mostly done verbally and not before PPAIW and is only based on mutual trust without any irar waqf deed as authentic evidence that the land has been waqfed for use in the public interest. As for the factors that cause the practice of waqf of ulayat land in Berampu sub-district, Dairi district are 1) Lack of public knowledge about waqf regulations in Indonesia. 2) The community still holds strongly to customs and habits that have been passed down from generation to generation. 3) The desire of the community to do charity through waqf institutions but not accompanied by knowledge.